Language as a Symbol of Social Status in Ama Ata Aidoo’s “For Whom Things Did Not Change” - Kademi, Abdullahi Salisu (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2022)
This study, conceived within the paradigm of sociolinguistics, examined the interplay between language and social status in a fictional work. Specifically, it investigated how language use gives a clue to the social status of characters in Ama Ata Aidoo’s “For Whom Things Did Not Change”, which is one of the short stories in her anthology, No Sweetness Here. The story was purposefully selected because of its fascinating language use. The qualitative research methodology was used in this study. Bickerton’s (1975), Creole Continuum and Adelugba’s (1981) analytical framework were used to characterize the language levels of the characters in the story. To make the analysis thorough, relevant literature and useful extracts from the short story were cited and discussed. Three levels of language corresponding to the social stratifications of the characters were found. Some of the characters were found to effortlessly oscillate between different linguistic varieties depending on the discourse situation, their roles, their perceived social status, and/or their interlocutors. The diversity of linguistic registers in the short story showed the differences between various characters in their classes, backgrounds, and educational status. It also reaffirms the notion that class hierarchies determine linguistic behaviour.